Vigil : a novel [large type] - Saunders, George, 1958- (Random House Large Print, 2026)
Jill Blaine, a supernatural guide, escorts the recently deceased to the afterlife. She is assigned to K. J. Boone, a man who has lived a remarkable and consequential life and faces his final evening without regrets. Visitors from various times and places, both living and supernatural, appear in his home, revealing moral, social, and environmental consequences of his actions. Themes include life and death, human responsibility, and ethical reflection. The narrative incorporates imaginative, surreal elements.